Professional integration of immigrant medical professionals through alternative career pathways: an Internet scan to synthesize the current landscape - Tanvir C. Turin; Nashit Chowdhury; Mark Ekpekurede; Deidre Lake; Mohammad Ali Ashraf Lasker; Mary O'Brien; Suzanne Goopy (BMC, 2021)
Abstract Background There is a growing recognition that underutilization and underemployment of skilled immigrants, especially internationally trained health professionals, creates a financial burden on individuals and economic losses for the host country. Albeit a missed opportunity for both the immigrants and the receiving country, no public policy and systemic measures are in place to address this issue. Nevertheless, certain individuals and organizations have made some isolated efforts, but no synthesized knowledge is available for understanding what initiatives exist altogether and how they function. We have conducted a methodological Internet scan to identify the existing individual, private, and systemic initiatives and resources that support these health professionals. This will provide health and workforce policymakers, settlement service providers, and relevant academics with the knowledge base for potential different strategies to address this issue and guide them towards developing solution-oriented initiatives. Methods To identify those we have systematically searched the three most popular search engines (Google, Bing, and Yahoo!) adapting the Canadian Institute for Health Information's grey literature review protocol. We identified relevant websites per our predefined inclusion criteria, charted the data from those sources, collated, summarized, and reported the results. Results From 280 webpages initially identified through keyword search, we included 26 in our full-page screen and extracted data from 16 finally selected webpages. We have found webpages with information on different alternative careers namely, regulated and non-regulated, available resources to pursue those careers, and what skills they have that can be transferred to the alternative careers. Conclusion More systemic policies and IMG specific and ACP-focused employment support programmes are required. Research and development of programmes for facilitating IMGs' alternative career support need to be increased and strengthened.